Building the gulf of opinions on the health and biological effects of electromagnetic radiation - Héroux, Paul (Frontiers in Public Health, 2025)
Using events that the author was personally involved with over many years, the article attempts to explain how different views solidified over time on the health effects of electromagnetic radiation, some believing they are negligible, while others believe they are substantial.